Is Platinum Present in Blood and Urine from Treatment Givers during Hyperthermic Intraperitoneal Chemotherapy?. (6th May 2010) - Näslund Andréasson, Sara; Anundi, Helena; Thorén, Sig-Britt; Ehrsson, Hans; Mahteme, Haile
Abstract : Background . In selected patients with peritoneal carcinomatosis (PC) originating from colorectal cancer (CRC) the high dosage of oxaliplatin (460 mg/m 2 ) is recommended for hyperthermic intraperitoneal chemotherapy (HIPEC), which may be a health risk to those administering the drug. The aim of this study was to determine the risk of platinum (Pt) exposure for the two main people handling and administering the cytotoxic agent during HIPEC. Methods . Samples of blood and urine were collected from one male surgeon and one female perfusionist during oxaliplatin-based HIPEC treatment with open abdomen coliseum technique on six consecutive patients with PC from CRC. Results . All blood samples analysed were below the detection limit of< 0.05  nmol/L Pt, and the urine samples were all below the detection limit of< 0.03  nmol/L Pt. Conclusions . There appears to be little or no risk of Pt exposure during HIPEC when the recommended protective garment is used and the safety considerations are followed.